What have we learned from mouse models for cystic fibrosis?. (July 2007) - Carvalho-Oliveira, Isabel; Scholte, Bob J; Penque, Deborah
Genetically modified mouse strains are important research tools for the study of numerous human diseases. These models provide us with differentiated tissues, which are not often available from human sources. Furthermore, they allow for testing the effects of genetic manipulation and experimental therapeutics on physiology and pathology. Their importance relies on the assumption that biological processes in the mouse very closely resemble those in humans. Cystic fibrosis (CF) is the most common lethal genetic disease in the Caucasian population. CF is a monogenic disease whose phenotype variability is also attributed to genetic variation in other genes, the so-called modifier genes. Modulation of such modifier genes could be a therapeutic strategy to treat CF. CF mice models have been essential not only for understanding the disease better, but also for the discovery of modifier genes and testing of chemical compounds developed to repair the main protein dysfunction in CF, the CF transmembrane conductance regulator. Mice were also indispensable in gene therapy trials and for the study of CF and non-CF lung response to bacterial infections and inflammation challenges, although no spontaneous lung disease is developed in these mice. In this review, mouse models and their most important contribution to the understanding and management of CF will be presented and discussed.